Impact of COVID-19 on the Sales Trend of E-commerce In Malaysia - Eugene Gan Hing Jian; Dong Ru Han; Du Guan Ting; Efa Afzan Bt Mohd Kamal Bahri; Mariajose Ruiz Atencio; A.A. Gde Satia Utama; James Perez-Moronnb (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2022)
On March 2020, the Coronavirus pandemic spread globally, and the tendencies have been profoundly altered. This pandemic also made doing business extremely tough. As international borders tighten, people around the world are forced to stay in their home and shops are closed, businesses are now facing new challenges and difficulties. Many businesses are facing closure either temporarily or permanently, leaving workers with months of financial burden and anxieties. Consumer behaviour was forced to alter on a massive scale. People in isolation or under lockdown cannot go about their daily lives because local businesses have been ordered to close for safety reasons. This paper investigates the current e-commerce trends in this Covid-19 pandemic, as well as how e-commerce advancements may affect customer behaviour in the future and the growth of e-commerce due to Covid-19. E-commerce has become a substitute in this pandemic and e-retailers must provide quality products that usually customers buy in physical stores traditionally.Â Keywords: Covid-19, E-Commerce, Pandemic, Sales Trend, E-Retailer